Effects of utterance rate and length on the spatiotemporal index in Parkinson's disease. - Chu, Shin Ying; Barlow, Steven M.; Lee, Jaehoon; Wang, Jingyan (International Journal of Speech-Language Pathology, 2020)
Purpose: To characterise labial articulatory pattern variability using the spatiotemporal index (STI) in speakers with idiopathic Parkinson's disease (PD) across different speaking rates and syllable-sentence conditions compared to age- and sex-matched healthy controls. Method: Ten speakers with mild–severe idiopathic PD and 10 controls produced "pa" and the Rainbow Passage at slow, typical and fast speech rates. Upper lip and lower lip kinematics were digitised during a motion capture system. Data were analysed using linear mixed modelling. Result: Regardless of the participant group, a high STI value was observed in the fast speech rate for the "pa" syllable condition, particularly for movements of the lower lip. As utterance rate increased, the control group showed the highest variability, followed by PD OFF and PD ON conditions. Syllable "pa" showed a greater STI value compared to both the first and second utterance of Rainbow Passage. Conclusion: PD manifests sufficient residual capacity to achieve near-normal motor compensation to preserve the consistency of lower lip movements during speech production. The lack of a significant difference in lip STI values between ON-OFF medication states suggests that dopaminergic treatment does not influence stability of speech for individuals with mild-moderate stage PD.